ADDRESSING CLIMATE CHANGE FOR SUSTAINABLE FOOD PRODUCTION IN NIGERIA - ABRAHAM, MELIGA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study investigated the impacts of climate change on food production systems in Nigeria and examines sustainable adaptation strategies to ensure food security. Through a systematic review and extensive literature analysis of peer-reviewed publications, government reports, and policy documents, the study identified key climate related challenges affecting Nigerian agriculture. Findings reveal that rising temperatures, irregular rainfall patterns, and increased frequency of extreme weather events have significantly reduced crop yields across major agricultural zones, with smallholder farmers experiencing disproportionate impacts due to limited adaptive capacity. The study identified several promising adaptation strategies, including climate-smart agriculture techniques, improved irrigation systems, drought-resistant crop varieties, and indigenous knowledge integration. Policy recommendations include strengthening agricultural extension services, developing weather-based insurance schemes, establishing early warning systems, improving access to climate finance, and integrating climate considerations into national agricultural policies.